Treating anaemia in chronic kidney disease improves cardiovascular outcome by improving left ventricular mass index - Rawat, Kavita J.; Joshi, Kavita S.; Arora, Rahul D. (International Journal of Advances in Medicine, 2016)
Background: Chronic kidney disease (CKD) has a high global prevalence of 11 to 13% with majority in stage 3.This has increased the burden on health care. Anaemia is important and independent risk factor for adverse cardiovascular outcome in CKD. Methods: Prospective observational study conducted over one year at KEM Hospital, Mumbai a tertiary care centre. Inclusion criteria were newly diagnosed patients with CKD above 18 years and excluded pregnant women, patients previously diagnosed as CKD, Ischemic heart disease and on maintenance haemodialysis. Complete haemogram, renal function tests, liver function tests, serum albumin, serum calcium, serum phosphorus, serum parathyroid hormone level, ECG and 2DEchocardiography were recorded. It was repeated at the end of one year after correcting Hb with human recombinant erythropoietin. Results: In all 102 patients, anaemia and left ventricular mass index (LVMI) are negatively correlated with each other at the start and end of the study with a correlation coefficient (r) of - 0.3 and 0.56 respectively. The change in haemoglobin and change in LVMI are also negatively correlated with correlation coefficient (r) of - 0.65. All the correlations are statistically significant. There was a significant improvement in haemoglobin, and there was a significant decrease in LVMI in all the patients. There was a partial regression in left ventricular hypertrophy with partial correction of anaemia in these patients. Conclusions: Anaemia and LVH in patients with CKD are negatively correlated. Treatment of anaemia with erythropoietin has been shown to induce a partial regression of LVMI.